The role of input and output in teaching English (Multidisciplinary Journal of Science and Technology, 2024)
The article discusses the importance of input and output in Teaching English to Speakers of Other Languages (TESOL). Input refers to the language that students are exposed to, while output refers to the language they use to communicate. The article highlights the role of input and output in language acquisition, emphasizing the need for a balance between the two. It also discusses the significance of communicative language teaching strategies and providing opportunities for students to practice speaking in real-world settings. Ultimately, the article concludes that effective language instruction involves both input and output, and that teachers should foster an environment that encourages students to engage in communicative activities.